Design and numerical modeling of a pressurized airframe bulkhead joint - Giannopoulos, Ioannis K.; Theotokoglou, Efstathios E.; Zhang, Xiang (AIAA, 2015)
The structural loading on a conceptual lap joint in the empennage of a civil aircraft has been investigated. The lap joint interfaces the end-pressure part-hemispherical bulkhead to the cylindrical fuselage. The pressure bulkhead is made of carbon fiber reinforced plastic materials. The aim of the study is to present numerical results of the induced structural loading from the fuselage positive internal pressure differential and the localized high stress intensity field at the lap joint location. A methodology for the appropriate numerical approach to analyze the domed pressure bulkhead is presented. The results of the numerical investigation showed that the laminate loading levels calculated by the use of either initial sizing analytical formulas for pressurized domes or by the use of equilibrium nodal loading from finite element models of low fidelity compared to refined finite element analysis can be significantly underestimated. Some of the implications on carbon fiber reinforced plastic structural sizing at the specified location are developed.